9 Bienal de São Paulo 1967 - Japão. - Bienal de São Paulo, 1967; Masuda, Yoshinobu (São Paulo : Bienal de São Paulo, 1967)
Amano, Kazumi ; Amano, Kunihiro ; Enokido, Maki ; Fukazawa, Yukio ; Fukita, Fumiaki ; Hagiwara, Hideo ; Hoshi, Joichi ; Kano, Mitsuo ; Kataoka, Tamako ; Kidokoro, Shô ; Kusaka, Kenji ; Maruki, Iri ; Miyashita, Tokio ; Murai, Masanari ; Sasajima, Kihei ; Shirai, Akiko ; Takagi, Shiro ; Yoshida, Hodaka ; Yoshida, Masaji ; Yoshihara, Hideo
biog. per kunstenaar
Engels & Portugees
IX Bienal de São Paulo 1967 Japão, São Paulo, 22.09.1967 - 08.01.1968
boek
Keywords: Japan